Efficiency enhancements in non-fullerene acceptor-based organic solar cells by post-additive soaking. Issue 15 (29th March 2019) - Choi, Hoyeon; Lee, Jihoon; Oh, Chang-Mok; Jang, Soyeong; Kim, Hyojung; Jeong, Mun Seok; Park, Sung Heum; Hwang, In-Wook
Abstract : Power conversion efficiency of non-fullerene acceptor-based organic solar cells based on PBDB-T : ITIC-m (1 : 1) composites has been successfully increased (from 9.6% to 12.3%) by using post-additive soaking (PAS) treatments on pristine BHJ films. Abstract : An improved efficiency of non-fullerene acceptor-based organic solar cells based on PBDB-T : ITIC-m composites has been obtained by using post-additive soaking (PAS) treatments on pristine BHJ films. The PAS-treated BHJ films show improved carrier dynamics in charge transfer and transport, leading to increased photocurrent and fill factors in the photovoltaic devices, followed by a high power conversion efficiency of 12.3%, which is an increase of 28% compared to that of the control device. We found that this superior performance predominantly resulted from improved exciton dissociation and enhanced electron transport after photoexcitation of the ITIC-m phase.